An enigma of Malaysia's low-income young adults: Mediation of financial behaviour on financial well-being and locus of control cohesion. - Mohamad Fazli Sabri; Rozita Wahab; Nurul Shahnaz Mahdzan; Amirah Shazana Magli; Husniyah Abd Rahim; Siti Shazwani Ahmad Suhaimi; Nur Shuhamin Nazuri (PLoS ONE)
Young adults face many significant challenges to their financial well-being. The rising cost of living and unstable economies have impacted how they consume, manage, and save monthly income to maintain their standard of living. Hence, exploring the financial well-being of young adults in Malaysia is an intriguing and relevant research topic that deserves examination from multiple perspectives. This study aims to investigate how these three factors, namely financial knowledge and locus of control with financial behaviour as a mediator, are correlated with the financial well-being of low-income young adults in Malaysia. A total of 520 young adults from North, Central, South, East zones in Peninsular Malaysia and East Malaysia were randomly chosen using a multi-stage sampling technique as the sample of this study. Data in this study were obtained using a set of questionnaire-based survey through cross-sectional study and then scrutinized using IBM SPSS (Statistical Package of Social Science). This study discovered that financial knowledge, internal and external locus of control, and financial behaviour were significantly correlated with the financial well-being of low-income young adults. The findings also demonstrate that financial behaviour mediates the correlation between financial knowledge, both internal and external locus of control, and financial well-being. This study is one of the very few important studies that explore the link between financial literacy, locus of control, financial behaviour, and financial well-being among low-income young adults. This study also found an interesting and noteworthy fact regarding the impact of the minimum monthly wage policy on highly educated young adults in Malaysia, which is worth discussing and needs to be alerted to the policymakers and leaders of the country. Therefore, the findings of this study can be utilized as a starting point by policymakers, government organizations, and non-governmental organizations to create new initiatives aimed at raising financial well-being among the younger generation.